Resíduos da indústria de beneficiamento de castanha de caju anarcadium occidentale l. como adsorvente de cromo (vi) em solução aquosa - Carvalho, Simone Cristina Freitas de (2021)
The increase in contamination of aquatic environments by toxic metals has as its main causes the disposal and inadequate treatment of industrial effluents. Chromium is a metal that stands out due to its various industrial applications, however, as it presents a high degree of toxicity, it is necessary to treat the effluent contaminated by chromium, before disposal. Several technologies have been used in the removal of toxic metals from effluents, among them; adsorption is considered promising, mainly due to the ability to remove pollutants in low concentrations and the possibility of using natural materials as adsorbents. The cashew nut shell is among the most versatile agricultural waste, mainly because it is a bio-based renewable material. Thus, the work aimed to evaluate the potential for adsorption of cashew nuts for use in the treatment of effluents containing chromium (VI). The bio adsorbents were obtained from the raw cashew nut shell (CN) and the processed cashew nut shell (CB). The techniques of scanning electron microscopy (SEM), x-ray diffraction (XRD), zero charge point (ZCP), Fourier transform infrared spectrometry (FTIR) and determination of functional groups by the Boehm method were used to characterize the adsorbents. The finite bath adsorption experiments evaluated the influence of pH, adsorption kinetics and thermodynamics. The maximum adsorption capacity of Cr (VI), obtained by the Langmuir model, was 236.67 mg/g for the CB adsorbent, and 221.97 mg/g for the CN adsorbent, for an adsorbent concentration of 4 g.L-1, at a pH of 1.0, a temperature of 38°C and a contact time of 3 h. The adsorption kinetics models were fitted to the experimental data, the Elovich model being the one that best described the adsorption kinetics of both adsorbents, characterizing chemisorption. The isotherm models were fitted to the adsorption equilibrium data, being evaluated for the best fit by the Akaike information criterion. The results were better described by the Langmuir and Sips isotherm models at different temperatures. The thermodynamic study indicated a spontaneous and endothermic adsorption process. It was also found that the process of adsorption of Cr (VI) in the adsorbents was favored by the increase in temperature. The results showed that the cashew nut shell has great potential to be used as adsorbent for the removal of chromium (VI)